Association between penultimate ejaculatory abstinence and sperm quality: a cross-sectional study - Jiang, Yuting; Zhu, Yueying; Kong, Qingkuo; Lv, Xin; Xi, Qi; Yu, Yang (Frontiers in Endocrinology, 2024)
Background Ejaculatory abstinence (EA) duration influences semen parameters. However, the impact of penultimate ejaculatory abstinence (PEA) on conventional and functional sperm parameters remains underexplored. Method A cross-sectional study recruited 1,503 men from a reproductive center between November 2023 and July 2024. Each participant underwent a physical examination, completed clinical questionnaires, and provided a semen sample for analysis. Generalized linear models were adjusted for potential confounders such as EA to investigate the association between PEA and various sperm parameters. Logistic regression was used to evaluate the relationship between PEA and the risk of high sperm DNA fragmentation index (DFI), oligozoospermia, asthenozoospermia, and necrozoospermia. Results Participants were categorized into four quartiles based on PEA duration. (Q1: 1-3 days; Q2: 4-5 days; Q3: 6-9 days; Q4: > 9 days). After adjusting for potential confounders, a significant positive linear association was found between PEA and DFI, while a significant negative linear association was observed with progressive sperm motility. The longest PEA duration (Q4) correlated positively with semen concentration (P = 0.025), total sperm count (P < 0.001), and sperm vitality (P < 0.001). Compared to Q1, a PEA of > 9 days (Q4) was associated with higher risks of sperm DFI > 30% (adjusted odds ratio [OR] = 4.25; 95% confidence interval [CI]: 2.37-7.62), asthenozoospermia (adjusted OR = 1.45; 95% CI: 1.07-1.96), and necrozoospermia (adjusted OR = 1.99; 95% CI: 1.07-3.69). Moreover, the risk of sperm DFI > 15% was higher in Q2, Q3, and Q4 compared to Q1. Conclusion Prolonged PEA adversely affects sperm DFI, progressive motility, and sperm vitality, increasing the likelihood of asthenozoospermia, necrozoospermia, and elevated DFI levels. These findings suggest that both EA and PEA should be considered in fertility assessments, with shorter PEA durations potentially yielding higher quality sperm, thereby enhancing male fertility evaluation and outcomes.